ELEMENTARY EFL STUDENTS’ ERRORS: HOW DOES THE TEACHER CORRECT STUDENTS’ ERRORS? - Jannah, Baiq Raudatul; Furaidah, Furaidah; Rachmajanti, Sri (Graduate School of Universitas Negeri Malang, 2020)
Abstract: Teacher?s corrective feedback on in English class has been studied many times in secondary or higher education level. However, how a teacher deliver corrective feedback in non-English subjects for students in elementary students rarely become the focus of studies. Therefore, this qualitative research studied the elementary students of International Class Program of SD Laboratorium UM. The second grader and the teachers contributed as the research subjects. There were five corrective feedback types used by the teacher, translation, first language, conversational recast, clarification, and explicit. Those feedbacks were considered as effective feedbacks since the students mostly responded to it.Abstrak: Penelitian tentang feedback korektif guru sebelumnya seringkali diteliti di pendidikan menengah atau di tingkat perguruan tinggi. Namun, bagaimana guru menyampaikan feedback korektif untuk siswa sekolah dasar pada pelajaran non-bahasa inggris sangat jarang dijadikan fokus penelitian. Maka dari itu penelitian ini mengkaji bagaimana guru memberikan korektif feedback pada siswa Program Kelas Internasional SD Laboratorium UM. Siswa kelas dua beserta gurunya menjadi subjek penelitian ini. Ada lima jenis feedback korektif yang diberikan guru; translation, first language, conversational recast, clarification, dan explicit. Feedback tersebut direspons oleh siswa.